Mentoring and Tacit Knowledge Transfer in Novice Teachers From Chinese Middle Schools: Mediating Effect of Job Crafting - Jiying Xu; Xueyan Wei; Robert D. Hisrich; Meifang Yu; Xue Li (Frontiers in Education, 2022)
In this study, we explore how mentoring relates to tacit knowledge transfer among middle school novice teachers in China and how job crafting mediates this relationship. In total, 465 Chinese novice teachers participated in this study and completed a set of self-reports measuring the mentoring function, tacit knowledge transfer, and job crafting. An analysis of the reports indicated that: (1) Mentoring, job crafting, and tacit knowledge transfer were positively correlated; (2) Four sub-factors of the mentoring function and five sub-factors of job crafting were significantly related to tacit knowledge transfer; (3) job crafting played a mediating role between mentoring and tacit knowledge transfer; (4) the mediating path of task crafting and skill crafting (two sub-factors of job crafting) between mentoring and tacit knowledge transfer was significant, while the mediating effect of role crafting, cognitive crafting, and relationship crafting (the other three sub-factors of job crafting) was not significant.